2022
DOI: 10.3390/foods11172556
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/Fs and DL-PCBs in Chinese Mitten Crab (Eriocheir sinensis) and Its Farming Environment in Shanghai, China

Abstract: Most polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and dioxin-like polychlorinated biphenyls (DL-PCBs) in the human body are acquired from dietary intake. The chronic exposure of humans to PCDD/Fs and DL-PCBs is a major health concern, and these compounds are strictly controlled in many areas. This study measured the levels of PCDD/Fs and DL-PCBs in Chinese mitten crab (Eriocheir sinensis) farms in Shanghai and determined potential sources. The mean concentrations of PCDD/Fs and DL-PCBs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…In the complex life cycle of the Chinese mitten crab, juveniles initiate upstream migration toward the limnic parental habitat after metamorphosis (Herborg et al, 2003). Similar behaviour of preferring fresh water was found in the megalopa of the Chinese mitten crab (Wang, 2012). Our experiment eliminated the influence of organic matter and the smell of natural seawater by using seawater solution mixed with sea salt and fresh water.…”
Section: Salinity Preferencesupporting
confidence: 56%
See 1 more Smart Citation
“…In the complex life cycle of the Chinese mitten crab, juveniles initiate upstream migration toward the limnic parental habitat after metamorphosis (Herborg et al, 2003). Similar behaviour of preferring fresh water was found in the megalopa of the Chinese mitten crab (Wang, 2012). Our experiment eliminated the influence of organic matter and the smell of natural seawater by using seawater solution mixed with sea salt and fresh water.…”
Section: Salinity Preferencesupporting
confidence: 56%
“…Most studies of Chinese mitten crabs were limited in salinity tolerance and stress in embryos, zoeae and adults (Normant et al, 2012;Wang et al, 2019). A previous study on the salinity preference of Chinese mitten crabs revealed that adult males did not demonstrate any preferences in the salinity range of 0-35 , but females preferred 21 (Wang, 2012). Although adult salinity selection and stress are documented, knowledge on juvenile salinity selection and other behavioural responses to salinity changes, especially the change in salinity selection after acclimation, is scant.…”
mentioning
confidence: 99%
“…More than 90% of human exposure to PCDDs/Fs and dl-PCBs originates from food, which has the lowest governmental regulatory concentration restriction among different media [ 53 , 54 ]. In the case of soil, the regulation level differs depending on the country or land use.…”
Section: Resultsmentioning
confidence: 99%